Caso de estudio de la aplicación de la metodología Six Sigma para mejorar el proceso de filete en la planta de costura de la empresa Colchones Spring S.A.S. (2000)
The following project presents the implementation of the Six Sigma methodology on the flanging process in the sewing factory of Colchones Spring S.A.S. The sections follow the DMAIC cycle, in which 1) the problem is defined 2) the current process is measured 3) the different possible causes that lead to the problem are analyzed and finally, a solution is proposed and an implementation plan is presented. The identified problem refers to the elevated number of mattress tops that do not satisfy the measure limits established by the company after the flanging process. More than 20% of these exceed the limits and need to be reprocessed. Initially, a 20% reduction in the faulty tops was proposed, but after selecting a solution and studying its potential, the results showed that there is a 50% potential reduction of faulty tops. This solution will reduce the number of tops that have to be reprocessed and destroyed, thus representing an increase in the active working time of the workers and a reduction in the cost associated to the destruction of tops.